2000
DOI: 10.1046/j.1365-3040.2000.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of yieldins regulating the yield threshold of cowpea cell walls: cDNA cloning and characterization of recombinant yieldin

Abstract: ABSTRACTcDNA for yieldin of Vigna unguiculata L. was cloned with reverse transcriptase-polymerase chain reaction using synthetic oligonucleotides as primers. The primers were designed on the basis of the N-terminal amino acid sequence of the yieldins isolated from the wall preparation of cowpea hypocotyls. The 1·2 kbp cDNA for yieldin contained an open reading frame of 981 base pairs, encoding 327 amino acids including 23 amino acids as a putative signal sequence. An homology search of the deduced amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
(46 reference statements)
3
21
0
1
Order By: Relevance
“…The reconstitution experiments on the heat-denatured GHC using recombinant yieldin showed that recombinant yieldin only fully restored the pH-dependent shift in y (Okamoto-Nakazato et al 2000b;Fig. 4).…”
Section: Molecular Cloning Of Yieldin 30mentioning
confidence: 98%
See 1 more Smart Citation
“…The reconstitution experiments on the heat-denatured GHC using recombinant yieldin showed that recombinant yieldin only fully restored the pH-dependent shift in y (Okamoto-Nakazato et al 2000b;Fig. 4).…”
Section: Molecular Cloning Of Yieldin 30mentioning
confidence: 98%
“…cDNA for yieldin was cloned with RT-PCR using synthetic oligonucleotides designed on the basis of the N-terminal amino acid sequence of purified yieldin 30 as a primer and total RNA extracted from the elongation region of cowpea hypocotyl as a template (Okamoto-Nakazato et al 2000b). The isolated 1.2-kbp cDNA for yieldin contained an open reading frame of 1,183 base pairs encoding 327 amino acids with a molecular mass of 35,647 Da.…”
Section: Molecular Cloning Of Yieldin 30mentioning
confidence: 99%
“…In embryogenic cultures of both D. carota and Picea abies, bacterial Nod factors can substitute for chitinases in their effect on early somatic embryo development (De Jong et al 1992;Egertsdotter and von Arnold 1998;Dyachok et al 2005). An acidic class III endochitinase (glycoside hydrolase family 18) from cowpea (Vigna unguiculata) was found to represent a protein that is required for cell wall loosening during acid growth (yieldin; OkamotoNakazato et al 2000a;2000b). Sasaki et al (2006) compared the substrate specificity of class I and class III chitinases from rice and found that the class III enzyme might act towards an endogenous complex carbohydrate containing a GlcNAc residue, but not against a GlcNAc oligomer or polymer, while the substrate of the class I enzyme was probably a consecutive GlcNAc sequence, maybe from the cell wall of a fungal pathogen.…”
Section: Roles Of Chitinases In Plantsmentioning
confidence: 99%
“…They are most active under acidic conditions. Recently, y proteins named yieldins were isolated from Vigna unguiculata L. hypocotyls (Okamoto-Nakazato et al 2000a) and their genes were cloned (Okamoto-Nakazato et al 2000b). The acidic environment is thought to activate cell wall loosening enzymes including f and y proteins (Taguchi et al 1999), resulting in cell wall loosening and hence cell wall expansion under the effective turgor pressure (P-y).…”
mentioning
confidence: 99%